The avengers: SAMHD1 cooperates with MX2/MxB to defend against HIV-1 - Zhi Wan; Gang Zhong; Huiqing Wang (mBio, 2024)
ABSTRACT SAMHD1 is an intrinsic limiting factor that effectively prevents HIV-1 infection in macrophages, dendritic cells, and resting CD4+ T cells. Extensive studies have underscored the indispensable role of the dNTPase activity of SAMHD1 in its antiviral function by primarily depleting dNTPs in quiescent cells, thereby impeding HIV-1 cDNA synthesis. However, recent advancements in understanding posttranslational modifications of SAMHD1 have revealed specific modification site mutants that maintain their ability to reduce dNTP levels while impairing the inhibition of HIV-1 replication. Thus, the precise anti-HIV-1 mechanism of SAMHD1 remains enigmatic, necessitating a comprehensive understanding of the underlying mechanisms to develop novel therapeutic strategies targeting its antiviral activity. Recent findings by Guo et al. shed light on the role of SAMHD1 as an HIV-1 core sensor in suppressing HIV-1 infection after viral cDNA synthesis through its interaction with MX2 (H. Guo, W. Yang, H. Li, J. Yang, et al., mBio 15:e01363-24, 2024, https://doi.org/10.1128/mbio.01363-24).